Teachers, Parents, and Netizens: Social Dynamics in Shaping a Nonviolent Education Paradigm in Indonesia - Nursalim (International journal of technology and education research, 2025)
The increasing number of reports filed by parents against teachers for alleged acts of violence toward students reflects a shifting value system and evolving power relations in Indonesia’s educational landscape. This issue transcends professional ethics and legal considerations, representing a broader social transformation influenced by public opinion in digital media. This study analyzes the roles of teachers, parents, and netizens in shaping a nonviolent education paradigm and examines how online discourse reconstructs authority within education. Using a qualitative descriptive approach, this research employs digital discourse analysis and targeted literature review of academic works, education policies, and social media posts (Twitter, Facebook, TikTok) published between 2020 and 2025. Data were thematically analyzed through the frameworks of Carl Rogers’s humanistic education theory and Paulo Freire’s critical pedagogy. The findings reveal three major themes: (1) the transformation of teacher–student relations toward empathy-based, nonviolent communication; (2) social media as a moral and ideological battleground redefining discipline and child protection; and (3) inconsistencies between child-friendly education policies and their practical implementation in schools. The study concludes that nonviolent education is not merely a normative ideal but a social process requiring a collective mindset shift, the integration of humanistic values into the curriculum, and the strengthening of ethical digital literacy across society. Its main contribution lies in integrating humanistic–critical pedagogical theories within Indonesia’s digital context, offering a triadic model of collaboration among teachers, parents, and the online public to build a peaceful and reflective education culture.